Peran Customer Information Dan Billing System Dalam Mendukung Kepuasan Pelanggan Di PDAM Tirta Manakarra Kabupaten Mamuju - Krisdayanti; Mayang; Yeni, Hari (CV. SINAR HOWUHOWU, 2026)
In the modern era, technology plays an increasingly significant role in supporting the efficiency of the public service sector. Customer Information & Billing Systems (CIBS) play an essential role in enhancing customer satisfaction by improving operational efficiency and billing accuracy. PDAM Tirta Manakarra, Mamuju Regency, faces challenges in managing customer information and billing systems. Recent research shows that the overall customer satisfaction level reached 58.22%, indicating that customers are quite satisfied, but there is still room for service improvement. Factors such as price, service quality, and word of mouth have a significant impact on customer satisfaction. This study aims to evaluate the impact of CIBS implementation on improving customer satisfaction levels at PDAM Tirta Manakarra and assess how this system improves operations and service quality as perceived by customers. CIBS implementation is expected to increase service efficiency and transparency, as well as support an enhanced customer experience. This study will analyze the role of CIBS in supporting customer satisfaction and recommend continuous improvement strategies based on case studies from various industries, including water services and telecommunications.